2009
DOI: 10.1038/ijo.2009.236
|View full text |Cite
|
Sign up to set email alerts
|

A mild favorable effect of soy protein with isoflavones on body composition—a 6-month double-blind randomized placebo-controlled trial among Chinese postmenopausal women

Abstract: Background: In vitro and animal studies suggested that soy protein and isoflavones promote weight and body fat loss. However, clinical trials in humans were few and the effects remained uncertain. Objectives: To examine whether soy protein with isoflavones and isoflavone extracts exert beneficial effects on body composition among postmenopausal women. Design: A double-blind randomized placebo-controlled trial was conducted among 180 postmenopausal Chinese women with mild hyperglycemia. After a 2-week adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 46 publications
1
26
3
Order By: Relevance
“…The green tea catechin EGCG has produced positive effects on body mass and composition in animals (Bose et al 2008;Ito et al 2008). Although quercetin had no effect on body mass or composition in the current study, small effects on body mass have been observed with tea catechins (Hase et al 2001;Nagao et al 2001Nagao et al , 2007Harada et al 2005) and other polyphenols such as soy flavonoids (Jenkins et al 2002;Liu et al 2009). However, Park et al (2008) found that a combination of genistein, quercetin, and resveratrol was more effective at inhibiting adipogenesis and inducing apoptosis in human adipocytes than any individual compound alone.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The green tea catechin EGCG has produced positive effects on body mass and composition in animals (Bose et al 2008;Ito et al 2008). Although quercetin had no effect on body mass or composition in the current study, small effects on body mass have been observed with tea catechins (Hase et al 2001;Nagao et al 2001Nagao et al , 2007Harada et al 2005) and other polyphenols such as soy flavonoids (Jenkins et al 2002;Liu et al 2009). However, Park et al (2008) found that a combination of genistein, quercetin, and resveratrol was more effective at inhibiting adipogenesis and inducing apoptosis in human adipocytes than any individual compound alone.…”
Section: Discussioncontrasting
confidence: 51%
“…The obesity pandemic has accelerated cell, animal, and human research on the anti-obesity effects of flavonoids (Borchardt and Huber 1975;Melzig 1996;Hase et al 2001;Nagao et al 2001Nagao et al , 2005Nagao et al , 2007Singh et al 2003;Alexander 2006;Greenberg et al 2006;Harwood et al 2007;Bose et al 2008;Egert et al 2008;Ito et al 2008;Stewart et al 2008;Liu et al 2009;Faria et al 2010;Grove and Lambert 2010;Zhu et al 2010). For example, several animal studies indicate that 3-15 weeks of supplementation with green tea extract and epigallocatechin gallate (EGCG) reduce body mass and fat mass (Bose et al 2008;Ito et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soy protein intake has been found to be related to a mild favorable effect on bone mass and weight reduction in postmenopausal Chinese women. [52][53] Being a high-quality protein source and containing isoflavones with estrogen-like effect, soy protein might contribute to the preserving effect of LM. More research on this area in perimenopausal women is warranted.…”
mentioning
confidence: 99%
“…However, soy protein and isoflavones of soybeans might play an important role. SupplementaInt J Food Nutr Sci | Volume 2: Issue 1 www.ommegaonline.com Soybean/Brown Rice Consumption in Postmenopausal Women tion with 15 g soy protein and 100 mg isoflavones affected the BW, BMI, and body fat reductions in Chinese postmenopausal women [17] . In our study, there were 8.7 ± 1.2 g of soy protein and 22.0 ± 3.0 mg of isoflavones in the SBR supplement; these contents were lower than supplements given in the above study.…”
Section: Discussionmentioning
confidence: 99%